Pengaruh Strategi Branding dan Penggunaan Sosial Media terhadap Peningkatan Penjualan di UMKM Kuliner di Medan Tembung - Raja Pratama Winfrid Hasibuan; Pesta Gultom; Lisa Elianti (Jurnal Minfo Polgan, 2026)
This study aims to analyze the effect of branding strategies and social media usage on sales growth among culinary MSMEs in Medan Tembung. Indonesia has significant potential in the Micro, Small, and Medium Enterprises (MSME) sector, which plays a vital role in driving the national economy. The success of MSMEs is often reflected in increased sales, as it indicates the ability of businesses to meet consumer needs and maintain sustainability. Sales growth can be influenced by several factors, including the implementation of effective branding strategies and the optimal use of social media as a promotional and communication tool. This research adopts a quantitative approach, utilizing both primary and secondary data. The sample consists of 72 culinary MSME owners in Medan Tembung. Data were collected through questionnaires using a Likert scale, supported by interviews and documentation. Data analysis was conducted using SPSS version 25, including validity, reliability, normality, multicollinearity, and heteroscedasticity tests, as well as multiple linear regression, t-test, F-test, and coefficient of determination (R²). The findings reveal that branding strategies have a positive and significant effect on sales growth, and social media usage also has a positive and significant effect on sales growth. Simultaneously, both variables significantly influence sales growth. The Adjusted R-Square value of 0.545 indicates that 54.5% of the variation in sales growth is explained by branding strategies and social media usage, while the remaining 45.5% is influenced by other factors outside this study.